Simulation Of Maleic Anhydride Production In Fixed Bed Reactor - Talib, Amirul Hakim Abd (Universiti Sains Malaysia, 2017)
In this study, simulation of partial oxidation n-butane was developed. Aspen Plus V8.8 was used for stimulated, analysed, and optimized process partial oxidation of n-butane and oxygen. N-butane feed to RPLUG model is equal to 0.0075 mole fraction and 0.21 mole fraction of oxygen which is rich oxygen state. Temperature and pressure of feed streams are set at 379.85°C and 1.6 atm. Diameter for reactor is 0.0025 m and length with 1.0 m. Catalyst used in the simulation is vanadium phosphorus oxide. Simulation of Aspen model was compare with literature to validate. Sensitivity was carried out with three different condition which is temperature, pressure, and feed flow rate. In optimization, the objective function is to maximize conversion of n-butane. The optimization give optimum value which is molar flow rate n-butane in at 0.001 kmol/hr and reactor temperature at 550°C.